Thermal Performance Evaluation of a Double Pipe Heat Exchanger Installed in a Biomass Gasification System - Nwabunwanne Nwokolo; Patrick Mukumba; KeChrist Obileke (Journal of Engineering)
Heat exchangers are widely used for heat recovery purposes in many industrial applications such as gasification systems. In a biomass gasification system situated at Melani village in Eastern Cape of South Africa, a significant quantity of heat energy is lost during syngas cooling. Thus, a heat exchanger was constructed and installed in the gasification system for the purpose of heat recovery. Therefore, the aim of this study is to evaluate the performance of the heat exchanger under variable operating conditions for counterflow and parallel flow configurations. The experimental investigation was carried out on a double pipe heat exchanger as the downdraft gasifier system operated on a wood consumption rate of 180 kg/h. The heat exchanger was installed at the exit point of the syngas in the gasifier, and water served as the cooling fluid. Inlet and outlet temperatures of the hot syngas and cooling water (fluids) were measured using thermocouples at variable flow rates. Experimental data were processed using energy equations to determine vital performance parameters (overall heat transfer coefficient, effectiveness, and log mean temperature difference). The findings showed that optimum heat exchanger effectiveness of 0.55 was determined at a mass flow rate of 0.07 kg/s. In addition, counterflow configuration was found to be approximately 14% more effective than the parallel flow configuration. This is attributed to the relative direction of the fluids in the configurations of both flows. The study recommends that double pipe heat exchanger is suitable for recovering heat from the gasification system.